Customized fiber glass posts. Fatigue and fracture resistance - Da Costa, Rogério Goulart; De Morais, Eduardo Christiano Caregnatto; Campos, Edson Alves [UNESP]; Michel, Milton Domingos; Gonzaga, Carla Castiglia; Correr, Gisele Maria (My University, 2012)
Purpose: To evaluate the root fracture strength of human single-rooted premolars restored with customized fiberglass post-core systems after fatigue simulation. Methods: 40 human premolars had their crowns cut and the root length was standardized to 13 mm. The teeth were endodontically treated and embedded in acrylic resin. The specimens were distributed into four groups (n=10) according to the restorative material used: prefabricated fiber post (PFP), PFP+accessory fiber posts (PFPa), PFP+unidirectional fiberglass (PFPf), and unidirectional fiberglass customized post (CP). All posts were luted using resin cement and the cores were built up with a resin composite. The samples were stored for 24 hours at 37°C and 100% relative humidity and then submitted to mechanical cycling. The specimens were then compressive-loaded in a universal testing machine at a crosshead speed of 0.5 mm/minute until fracture. The failure patterns were analyzed and classified. Data was submitted to one-way ANOVA and Tukey's test (α= 0.05). Results: The mean values of maximum load (N) were: PFP - 811.4 ± 124.3; PFPa - 729.2 ± 157.2; PFPf- 747.5 ± 204.7; CP - 762.4 ±110. Statistical differences were not observed among the groups. All groups showed favorable restorable failures. Fiberglass customized post did not show improved fracture resistance or differences in failure patterns when compared to prefabricated glass fiber posts.